PENGARUH STRUKTUR CORPORATE GOVERNANCE TERHADAP INTEGRITAS LAPORAN KEUANGAN (Survei pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2012 – 2015) - Bambang Widarno, Putri Lestari, Fadjar Harimurti & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2018)
The purpose of this study to determine the significance of the effect of structure corporate governance on financial statement integrity. This research is a case study in Indonesia Stock Exchange (BEI) year 2012 - 2015. Sources of data used are secondary data. A sample of 11 employees with purposive sampling. Methods of data collection used literature study. Data analysis techniques used multiple linear regression. The results show that independent commissioners, managerial ownership, institutional ownership, and audit committee have no significant effect on the integrity of financial statementsKeywords: independent commissioners, managerial ownership, institutional ownership, audit committees, financial statement integrity